왕고들빼기, 갯기름나물, 곤달비, 곤드레의 채종시기가 종자 생산성에 미치는 영향 - 서현택; Hyun Taek Seo; 김세원; Se Won Kim; 문윤기; Youn Gi Moon; 박기덕; Ki Duk Park; 박기진; Ki Jin Park (농업생명환경연구, 2022)
This study was conducted to investigate the effects of the timing of seed harvest on the seed productivity of Wang-godeulppaegi [Lactuca indica var. laciniata (O. Kuntze) Hara], Gaesgileumnamul (Peucedanum japonicum Thunb.), Gondalbi [Ligularia stenocephala (Maxim.) Matsum], and Gondeule [Cirsium setidens (Dunn) Nakai] . Wang-godulpagi and Gondeule were harvested at 15, 30, and 45 days after flowering; Gondalbi was harvested at 30, 45, and 60 days after flowering; and seaweed was harvested after 45, 60, and 90 days. In both the field and greenhouse, total and product seeding amounts were highest in the treatment area 30 days after flowering. The yield of products per 10a under field cultivation was high in the order 30 > 15 > 45 days after flowering. Comparatively, higher yields were obtained at the same time points under greenhouse cultivation. Under both field and greenhouse cultivation, the total and commercial yields of Gondeule were highest in the treatment area 30 days after flowering. Yield of products per 10a under field cultivation was high in the order 30 > 15 > 45 days after flowering, and again higher yields were obtained under greenhouse cultivation. For Gondalbi, the highest total and commercial yields under both field and greenhouse cultivation were obtained at 45 days after flowering in the order 45 > 60 > 30 days after flowering, with higher yields being obtained under greenhouse cultivation. For Gaesgileumnamul, the highest total and product yields under both field and greenhouse cultivation were obtained at 60 days after flowering, with higher yields being obtained under greenhouse cultivation. On the basis of these findings, it was considered suitable to harvest Wang-godeulppaegi and Gondeule after cutting at 30 days after flowering. In contrast, for Gondalbi and Gaesgileumnamul, seed productivity could be enhanced by delaying harvesting until approximately 45 and 60 days after flowering, respectively.